Structural competency in emergency medicine services for transgender and gender non-conforming patients. (February 2019) - Willging, Cathleen; Gunderson, Lara; Shattuck, Daniel; Sturm, Robert; Lawyer, Adrien; Crandall, Cameron
Abstract: In this formative qualitative research, we draw upon the concepts of structural vulnerability and structural competency to examine how transgender and gender non-conforming (TGGNC) patients and healthcare personnel experience service delivery in Emergency Departments (EDs), and how this experience can be improved upon. Between October 2016 and June 2017, we undertook 31 semi-structured interviews with TGGNC patients (n = 11) and physicians (n = 6), nurses (n = 7), and non-clinical staff (n = 7) in four community-based EDs in New Mexico. Our iterative coding and analysis process resulted in eight sets of findings: (1) reasons why TGGNC patients seek care from EDs; (2) perceptions about and experiences of TGGNC patients; (3) relevance of gender identity and sex at birth; (4) bureaucracy and communication; (5) spatial considerations; (6) preparing providers and staff to care for TGGNC patients; (7) the lack of resources for structural prescriptions; and (8) respect, humanity, and sameness. Findings suggest that structural issues adversely impact the health and wellbeing of TGGNC patients and service-delivery practices in the ED. We describe study implications for training ED personnel and modifying this practice setting to prevent delayed care and ensure appropriate services for TGGNC patients in need of structurally competent emergency medicine. Highlights: Examines care delivery for transgender patients in emergency departments. Emphasizes structural vulnerabilities causing health disparities for transgender patients. Advocates for structural competency education to promote greater equity in emergency services. Stresses structural solutions to health disparities for transgender patients. Argues for adaptations in clinical systems to improve care for transgender patients.